Harmonization of Halal Certification in Indonesia with Maqashid Syariah Principles: an In-Depth Study of Jasser Auda's System Approach - Syihabuddin, Muhammad; Suwandi, Suwandi (TAWAZUN: Journal of Sharia Economic Law, 2024)
The phenomenon of halal certification in Indonesia has become a public spotlight in the face of the complexity of the industrial world. The principle of Maqashid Sharia, which puts forward the highest goals in Islamic law to protect and promote the welfare of mankind, has become a critical foundation in the effort to achieve harmony between religious requirements and the practical needs of industry. Through a systematic system approach, Jasser Auda is expected to be the ideal foundation for integrating Islamic law based on Maqashid Sharia with halal certification. This study used a literature research method involving primary sources, namely Jasser Auda's book entitled "Maqasid Al-Shariah as Philosophy of Islamic Law: a Systems Approach" and as a secondary source of research related to the discussion of halal certification in Indonesia. The results of this study revealed three things: 1) The relationship between sharia maqashid and halal certification is very visible and includes five important points in maqashid, namely religious protection (hifz ad-din), soul (hifz an-nafs), reason (hifz al-Aql), offspring (hifz an-Nasl), and property (hifz al-Mal).  2) Through 6 features in Auda's thinking system approach, it is very helpful in harmonizing the existence of a halal certification program. This is through many considerations and the role of all stakeholders in order to achieve the objectives of halal certification in accordance with maqashid sharia. 3) The dynamics of the existence of halal certification are certainly faced with various problems, thus an integrative approach is needed in an effort to achieve effective and inclusive harmonization for all parties.